2021
DOI: 10.1021/acs.joc.1c01026
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Fused Isocoumarins via Palladium-Catalyzed Annulation of Alkyne-Tethered Malononitriles

Abstract: An enantioselective palladium-catalyzed annulation of alkyne-tethered malononitriles for the synthesis of 3,4-ring-fused isocoumarins is described. This cascade strategy involves oxypalladation of ortho-alkynylbenzoates and desymmetrizing addition onto one cyano group of the pendant malononitriles, which enables the concurrent construction of two rings and an all-carbon quaternary stereocenter in a single operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In 2021, these authors applied the same chiral ligand to promote related enantioselective palladium‐catalyzed annulation of other alkyne‐tethered malononitriles 152 (Scheme 39). [49] In this case, only 6 mol% of chiral phosphinooxazoline ligand 149 combined with 5 mol% of Pd(TFA) 2 as precatalyst were sufficient to promote the cascade reaction performed in THF as the solvent at lower reaction temperature (60 vs 100 °C). In the presence of TsOH⋅H 2 O as additive, the domino reaction of diversely substituted methyl o ‐alkynylbenzoates 152 evolved through successive oxypalladation and intramolecular nitrile addition, delivering the corresponding chiral 3,4‐ring‐fused isocoumarins 153 exhibiting a nitrile‐containing quaternary stereogenic center with moderate to good yields (34–75%) and high ee values (74–98% ee ).…”
Section: Enantioselective Palladium‐catalyzed Domino Reactionsmentioning
confidence: 97%
“…In 2021, these authors applied the same chiral ligand to promote related enantioselective palladium‐catalyzed annulation of other alkyne‐tethered malononitriles 152 (Scheme 39). [49] In this case, only 6 mol% of chiral phosphinooxazoline ligand 149 combined with 5 mol% of Pd(TFA) 2 as precatalyst were sufficient to promote the cascade reaction performed in THF as the solvent at lower reaction temperature (60 vs 100 °C). In the presence of TsOH⋅H 2 O as additive, the domino reaction of diversely substituted methyl o ‐alkynylbenzoates 152 evolved through successive oxypalladation and intramolecular nitrile addition, delivering the corresponding chiral 3,4‐ring‐fused isocoumarins 153 exhibiting a nitrile‐containing quaternary stereogenic center with moderate to good yields (34–75%) and high ee values (74–98% ee ).…”
Section: Enantioselective Palladium‐catalyzed Domino Reactionsmentioning
confidence: 97%
“…In addition to the asymmetric amino-palladation/desymmetrizing nitrile addition cascade reaction, Liu's group showed that Pd-( S )- t Bu-Phox complexes described in Scheme 82 also served as effective catalysts for the oxy-palladation/desymmetrizing nitrile addition cascade reaction, allowing for the efficient synthesis of chiral 3,4-ring-fused isocoumarins 494 (Scheme 113). 228 Various substituents on the benzoate moiety were amenable to this transformation, except for sterically bulky ortho -methyl-substituted benzoates which failed to yield the expected product. The ester groups substituted with methyl and ethyl proceeded smoothly whereas the tert -butyl ester substrate resulted in a dramatically reduced yield.…”
Section: Cyclization Initiated By Heteropalladation Of Triple Bondsmentioning
confidence: 99%
“…Subsequent hydrolysis of W by aqueous HCl produced the final carbazolone. In addition, the same catalyst system was applied to develop enantioselective annulation of other alkynetethered malononitriles 105 (Scheme 28) [42]. In this case, only 5 mol% of Pd(TFA)2 was sufficient in combination with 6 mol% of chiral phosphinooxazoline ligand 102 to induce the cascade reaction performed in THF (tetrahydrofuran) as the solvent at a lower temperature (60 vs 100 °C).…”
Section: Tricyclic Moleculesmentioning
confidence: 99%